Relationship between Quality Control and Customer Satisfaction - Shinta Wulan; Fahril Azizah (FEBI UIN Sunan Kalijaga, 2021)
The use of Total Quality Management (TQM) in a company or organization is one of the actions taken by a company or organization to achieve customer satisfaction. This is usually done by the company by adding quality to the internal company. If the internal can be well, it is expected that the external will also be good. In its aim Total Quality Management (TQM) has a long term, Total Quality Management (TQM) focuses on quality, based on the participation of all its members. Total Quality Management (TQM) uses effective strategies, data and communication to integrate quality discipline into the culture and activities of the company. The basic philosophy of Total Quality Management (TQM) is as an effect of customer satisfaction, a company or organization can experience success. Total Quality Management (TQM) can be widely used in manufacturing, education, government and service industries. So Total Quality Management (TQM) is used by companies to improve internal company in customer satisfaction.